Studies of the relations between the content of macrocycles and the performance among 22 elite swimmers - Hellard, P.; Gozelan, P.; Lacoste, L.; Barale, F.; Rey, J. L.; Fauquet, C. (First international symposium sciences and practices in swimming, 2006)
We set out to study the middle term effects of training on the performance of 22 elite swimmers. For this purpose, we linked the content of 2 winter macrocycles (M1, September-December; M2, January-April) to the evolution of performances between the first and second macrocycles by means of correlations and multiple regressions. The results of the regressions among women showed that the most significant performance enhancements were associated to a short M1 with a high mileage and a training focusing on aerobic/anaerobic threshold in M2 (r2=0.94, F=32.83, p < 0.001). In the men's case, the most important performance improvements were linked to a high volume of leg training and a low number of competitions in M1 together with a high volume of specific anaerobic training and a low volume in leg training for M2 (^=0.99, F=106, p < 0.001).